The case of paroxysmal kinesigenic dyskinesia: a long way from a symptom to the diagnosis - N. L. Kim; M. A. Yamin (Alʹmanah Kliničeskoj Mediciny, 2021)
Paroxysmal kinesigenic dyskinesia belongs to the group of primary dyskinesias, which also includes paroxysmal non-kinesigenic dyskinesia and exercise-induced paroxysmal dyskinesia. Due to the rarity of this disease group, as well as to the existence of a wide spectrum of disorders associated with transient movement abnormalities, the diagnosis is often difficult. A thorough analysis of clinical presentation, objective registration of paroxysmal events (video-electroencephalography monitoring) is helpful in the diagnosis. The most common causes of paroxysmal kinesigenic dyskinesia are mutations in the PRRT2 gene, while paroxysmal non-kinesigenic dyskinesia is caused by the MR1 gene mutations.The paper describes a clinical case of a 13 year old patient with acute, movement-associated, shortterm dystonic, choreic and ballistic hyperkinesis attacks. The patient had been treated with the diagnosis of epilepsy, tics, and dystonia for a long time without any effect. During diagnostic workup, a mutation in the PRRT2 gene intron was identified by a new generation sequencing of gene panel. Despite of this mutation has not been previously described, taking into account the type of Informed consent statement hyperkinesis attacks, association of their onset to movements, as well as the data of instrumental assessments, the diagnosis of paroxysmal kinesi-genic dyskinesia was made. Treatment with carbamazepine was successful with complete control over hyperkinesis.The diagnosis of paroxysmal dyskinesias remains based on the analysis of clinical picture and the trigger type. Molecular genetic diagnostics, with consideration of the most frequent causal mutations related to these conditions, can minimize both time and financial costs.